Second cancers in MPN: Survival analysis from an international study. Issue 3 (22nd December 2019) - Marchetti, Monia; Ghirardi, Arianna; Masciulli, Arianna; Carobbio, Alessandra; Palandri, Francesca; Vianelli, Nicola; Rossi, Elena; Betti, Silvia; Di Veroli, Ambra; Iurlo, Alessandra; Cattaneo, Daniele; Finazzi, Guido; et al.
Abstract: One out of ten patients with Philadelphia‐negative myeloproliferative neoplasms (MPN) develop a second cancer (SC): in such patients we aimed at assessing the survival impact of SC itself and of MPN‐specific therapies. Data were therefore extracted from an international nested case‐control study, recruiting 798 patients with SC diagnosed concurrently or after the MPN. Overall, 2995 person‐years (PYs) were accumulated and mortality rate (MR) since SC diagnosis was 5.9 (5.1‐6.9) deaths for every 100 PYs. A "poor prognosis" SC (stomach, esophagus, liver, pancreas, lung, ovary, head‐and‐neck or nervous system, osteosarcomas, multiple myeloma, aggressive lymphoma, acute leukemia) was reported in 26.3% of the patients and was the cause of death in 65% of them (MR 11.0/100 PYs). In contrast, patients with a "non‐poor prognosis" SC (NPPSC) incurred a MR of 4.6/100 PYs: 31% of the deaths were attributed to SC and 15% to MPN evolution. At multivariable analysis, death after SC diagnosis was independently predicted (HR and 95% CI) by patient age greater than 70 years (2.68; 1.88‐3.81), the SC prognostic group (2.57; 1.86‐3.55), SC relapse (1.53; 10.6‐2.21), MPN evolution (2.72; 1.84‐4.02), anemia at SC diagnosis (2.32; 1.49‐3.59), exposure to hydroxyurea (1.89; 1.26‐2.85) and to ruxolitinib (3.63; 1.97‐6.71). Aspirin was protective for patients with a NPPSC (0.60; 0.38‐0.95). In conclusion, SC is a relevant cause of death competing with MPN evolution. Prospective data are awaited to confirm the role of cytoreductive and anti‐platelet drugs in modulating patient survival after the occurrence of a SC.